A four-year observation of HIV and sexually transmitted infections among men who have sex with men before and during pre-exposure prophylaxis in Tokyo. Issue 6 (June 2022) - Mizushima, Daisuke; Takano, Misao; Ando, Naokatsu; Uemura, Haruka; Yanagawa, Yasuaki; Aoki, Takahiro; Watanabe, Koji; Ishizuka, Naoki; Oka, Shinichi
Abstract: Background: Pre-exposure prophylaxis (PrEP) with tenofovir/emtricitabine (TDF/FTC) has been recommended worldwide. We evaluated the safety and efficacy of daily PrEP with TDF/FTC in Tokyo. Methods: This single-center, single-arm study was performed with 124 men who have sex with men (MSM) between January 2017 and March 2021. MSM who entered into an MSM cohort from January 2017 through March 2018 and had a pre-PrEP observational period of 1 year were eligible and recruited to the study between April 2018 and March 2019 and followed for 2 years. The primary outcome was the incidence of HIV infection (per 100 person-years). Secondary outcomes were the incidence of sexually transmitted infections and adverse events, and the rate of retention and adherence to PrEP. Results: There were 309 MSM registered in the cohort (mean age, 36.6 years); 124 fulfilled the criteria and were included in the study. The remaining patients were continuously followed. There was a significant decrease in incidental HIV infection among PrEP users (0 infections, 235.5 person-years) compared to non-PrEP users (11 infections [3.4%/year], 318.9 person-years; p = 0.01). The average adherence rate was consistently greater than 95%, and the retention rate at two years was approximately 80%. Conclusions: The present study showed a high prophylactic effect against HIV infection, retention, and adherence to PrEP. PrEP is feasible and highly recommended in Japan. Trial registration: UMIN Clinical Trials Registry (UMIN000031040, www.umin.ac.jp ), Japan Registry of Clinical Trials (jRCTs031180134).